Inhibiting DNA methylation improves antitumor immunity in ovarian cancer - Katherine B. Chiappinelli; Stephen B. Baylin (The Journal of Clinical Investigation, 2022)
Cancer cells resist the immune response in a process known as immune editing or immune evasion. Therapies that target the immune system have revolutionized cancer treatment; however, immunotherapies have been ineffective for the majority of ovarian cancer cases. In this issue of the JCI, Chen, Xie, et al. hypothesized that hypomethylating agent (HMA) treatment would induce antitumor immunity to sensitize patients with ovarian cancer to anti-PD-1 immunotherapy. The authors performed a phase II clinical trial to test the combination of guadecitabine, a second-generation HMA, along with pembrolizumab, an immune checkpoint inhibitor of PD-1. The trial included a group of 35 patients with platinum-resistant ovarian cancer. While the clinical benefit from the combined HMA plus immune checkpoint blockade regimen was lower than hoped, the correlate analyses gave important information about which patients with ovarian cancer may be more likely to respond to immune therapy.